Construction of Carbon Dots with Color‐Tunable Aggregation‐Induced Emission by Nitrogen‐Induced Intramolecular Charge Transfer. Issue 49 (13th October 2021) - Xu, Xiaokai; Mo, Luoqi; Li, Yadong; Pan, Xiaoqin; Hu, Guangqi; Lei, Bingfu; Zhang, Xuejie; Zheng, Mingtao; Zhuang, Jianle; Liu, Yingliang; Hu, Chaofan
Abstract: As one of the most promising fluorescent nanomaterials, the fluorescence of carbon dots (CDs) in solution is extensively studied. Nevertheless, the synthesis of multicolor solid‐state fluorescence (SSF) CDs is rarely reported. Herein, CDs with multicolor aggregation‐induced emission are prepared using amine molecules, all of them exhibiting dual fluorescence emission at 480 nm (Em‐1) and 580–620 nm (Em‐2), which is related to the SS bonds of dithiosalicylic acid and the conjugated structure attached to CO/CN bonds, respectively. As a strong electron‐withdrawing group, the increase of CN content makes dual‐fluorescent groups on the surface of CDs produce push and pull electrons, which determines intramolecular charge transfer (ICT) between the double emission. With the increase in CN content from 35.6% to 58.4%, the ICT efficiency increases from 8.71% to 45.94%, changing the fluorescence of CDs from green to red. The increase of ICT efficiency causes fluorescence quantum yield enhancement by nearly five times and redshift of the fluorescence peak. Finally, based on the multicolor luminescence properties induced by the aggregation of CDs, pattern encryption and white‐LED devices are realized. Based on the fat solubility and strong ultraviolet absorption characteristics of CDs, fingerprint detection and leaf anti‐UV hazards are applied. Abstract : Carbon dots (CDs) with multicolor aggregation‐induced emission exhibit dual fluorescence emission at 480 and 580 nm, which is related to the SS bonds of DTSA and the conjugated structure attached to CO/CN bonds, respectively. With the increase of CN content from 35.6% to 58.4%, the intramolecular charge transfer efficiency increases from 8.71% to 45.94%, changing the fluorescence of the CDs from green to red.